2010
DOI: 10.1007/s11262-010-0554-8
|View full text |Cite
|
Sign up to set email alerts
|

High sequence conservation among Odotoglossum ringspot virus isolates from orchids

Abstract: The variability in the nucleotide (nt) and amino acid (aa) sequences of the coat protein (CP) of Odontoglossum ringspot virus (ORSV), which naturally infects orchids worldwide, was investigated. The CP genes of 48 ORSV isolates originating from different locations in Korea were amplified using RT-PCR and sequenced. The encoded CP consists of 158 aa. The CP sequences of the Korean isolates were compared at the nt and aa levels with those of the previously published ORSV isolates originating from different count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
(36 reference statements)
1
8
0
Order By: Relevance
“…Our previous results also showed that a number of ORSV isolates caused severe damage in orchid production [21]. Among the larger population of samples showing positive reactions, the nt sequences of the CP genes of 55 Korean isolates were further determined in this study.…”
Section: Resultsmentioning
confidence: 78%
“…Our previous results also showed that a number of ORSV isolates caused severe damage in orchid production [21]. Among the larger population of samples showing positive reactions, the nt sequences of the CP genes of 55 Korean isolates were further determined in this study.…”
Section: Resultsmentioning
confidence: 78%
“…; Yoon et al. ). A possible reason was that the genetic functional constraints may limit variability (Alonso et al.…”
Section: Resultsmentioning
confidence: 97%
“…; Yoon et al. , ), but little is known about ORSV and CymMV isolates in Guangdong Province, China. In this study, the coat protein (CP) gene sequences of CymMV and ORSV isolates from different orchid genera in Guangdong were detected and determined.…”
Section: Introductionmentioning
confidence: 99%
“…The only effective control of ORSV is through the use of host plant genetic resistance, either conventional or transgenic (Ajjikuttira et al, 2002; Yoon et al, 2011). Hence, it is very important to understand the molecular variability, divergence, and migration of ORSV population in each region.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies reported the genetic variability of ORSV isolates from Korea (Ajjikuttira et al, 2002; Yoon et al, 2011) and China (Rao et al, 2015). These showed high sequence conservation in CP gene.…”
mentioning
confidence: 99%